The Effect of Specific Drills on Some Physical Attributes and Basic Skills for Al Muthanna University Women’s Futsal Team - Hammood, Anwar Abdul Hadi (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of the study: Identifying the effect of specific drills on some physical attributes and basic skills for Al Muthanna University Women’s Futsal Team. Identifying the differences between the two study groups in terms of the some physical attributes and basic skills for Al Muthanna University Women’s Futsal Team. The researchers have used an empirical approach with two equivalent groups to carry out the study. The sample of the study was a twelve futsal female player team of Al Muthanna University. The necessary relevant information has been collected as well as several field procedures, such as verifying the validity of the tests, have been conducted. Having done that, the researchers have conducted pretests for both experimental and control group, then the two groups have practiced the indicated specific drills as required, that is, the experimental group has tried the specific drills that are already made by the researchers. While the control one has tried the specific drills that are made by the coach of the team. Having done that, posttests have been conducted. Then, the relevant statistical means have been used to calculate and analyze the data. As a result, the researchers have come to conclude that the practiced specific drills have a significant effect on some physical attributes and basic skills for Al-Muthanna University Women’s Futsal Team.